2019
DOI: 10.1103/physrevb.99.104424
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure and spin-flop transition in the A -site columnar-ordered quadruple perovskite TmMn3O6

Abstract: We present the magnetic structure of TmMn3O6, solved via neutron powder diffraction -the first such study of any RMn3O6 A-site columnar-ordered quadruple perovskite to be reported. We demonstrate that long range magnetic order develops below 74 K, and at 28 K a spin-flop transition occurs driven by f -d exchange and rare earth single ion anisotropy. In both magnetic phases the magnetic structure may be described as a collinear ferrimagnet, contrary to conventional theories of magnetic order in the manganite pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…The refined magnetic structure is consistent with the collinear ferrimagnetic phase found in Tm 2 MnMnMn 4 O 12 [17] and R 2 CuMnMn 4 O 12 [18]. Moment orientations of m||[x, 0, 0], m||[x, x, 0], or m||[x, y, 0] correspond to different magnetic symmetries described by the three distinct order-parameter directions of the + 5 irrep (see Tables III, IV, and V of Appendix A); however, these three cases cannot be differentiated by our neutron-diffraction data due to powder averaging in the tetragonal crystal symmetry.…”
Section: (A)supporting
confidence: 79%
See 3 more Smart Citations
“…The refined magnetic structure is consistent with the collinear ferrimagnetic phase found in Tm 2 MnMnMn 4 O 12 [17] and R 2 CuMnMn 4 O 12 [18]. Moment orientations of m||[x, 0, 0], m||[x, x, 0], or m||[x, y, 0] correspond to different magnetic symmetries described by the three distinct order-parameter directions of the + 5 irrep (see Tables III, IV, and V of Appendix A); however, these three cases cannot be differentiated by our neutron-diffraction data due to powder averaging in the tetragonal crystal symmetry.…”
Section: (A)supporting
confidence: 79%
“…Here, both A-B and B-B d-d superexchange interactions are present, and the a + a + c − tilts remove A-A d-d superexchange pathways, which are then reduced to super-superexchange. The weakness of A-A d-d exchange has recently been demonstrated in (NaDy)MnMnTi 4 O 12 [16], where in the absence of A-B and B-B interactions (B = Ti 4+ ), antiferromagnetic order develops on the A-site sublattices only below 12 K. To the contrary in Tm 2 MnMnMn 4 O 12 , the presence of both A-B and B-B exchange stabilizes ferrimagnetic order below 74 K, with a ferromagnetic B-site sublattice that is in direct contradiction to the C-type antiferromagnetic B-site sublattice theoretically predicted by B-B exchange alone-a state that is instead thought to arise as a result of A-B exchange dominating over both A-A and B-B exchange [17]. Indeed, it was shown that when A-B exchange is weakened by substituting Cu 2+ for Mn 3+ on the A sites (R 2 CuMnMn 4 O 12 , R = Dy and Y), antiferromagnetic spin canting is introduced onto the B-site sublattice [18].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…50% of doping can result in the so-called A-site columnarordered quadruple perovskites with a general composition of A 2 A A B 4 O 12 [19], where a square-planar A site is usually occupied by Cu 2+ , Mn 2+ , and Mn 3+ , and a tetrahedral A site by Mn 2+ . Mn cations at three A , A , and B sites can order at the same time, for example, at T N,Mn = 74 K in TmMn 3 O 6 [20] and at T N,Mn = 76 K in NdMnMnSbO 6 [21], while rareearth cations at the A site usually order at lower temperatures: T N,Tm = 28 K in TmMn 3 O 6 and at T N,Nd = 42 K in NdMnMnSbO 6 . Note that in this subfamily of perovskites, the T N,R /T N,Mn ratio is noticeably higher than that of other subfamilies reported so far, and it can even reach unity.…”
Section: Introductionmentioning
confidence: 99%